2020
DOI: 10.1186/s12938-020-00827-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of safety for electrochemotherapy and irreversible electroporation ablation therapies in patients with cardiac pacemakers

Abstract: Background The effectiveness of electrochemotherapy of tumors (ECT) and of irreversible electroporation ablation (IRE) depends on different mechanisms and delivery protocols. Both therapies exploit the phenomenon of electroporation of the cell membrane achieved by the exposure of the cells to a series of high-voltage electric pulses. Electroporation can be fine-tuned to be either reversible or irreversible, causing the cells to either survive the exposure (in ECT) or not (in IRE), respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Prior study of high-voltage electroporation pulses used in other fields such as oncology has been performed in patients with CEIDs without any effect on the device parameters [16]. According to our ablation protocol, PFA should not be performed with direct contact to the CIEDs or other devices.…”
Section: To Avoid Interactions Between Catheter Ablation and Ciedsmentioning
confidence: 99%
“…Prior study of high-voltage electroporation pulses used in other fields such as oncology has been performed in patients with CEIDs without any effect on the device parameters [16]. According to our ablation protocol, PFA should not be performed with direct contact to the CIEDs or other devices.…”
Section: To Avoid Interactions Between Catheter Ablation and Ciedsmentioning
confidence: 99%
“…85 The factors that can limit the use of ECT include the size of the tumor 89 and difficult accessibility of a tumor by electrodes For safety reasons, ECT is currently contraindicated for patients with cardiac pacemakers and patients on anticoagulant therapy. 3,90…”
Section: Electrochemotherapymentioning
confidence: 99%
“…In cardiology, the pulsed-field ablation has been receiving larger attention as an ablative modality that uses short living, the strong electrical field created around the catheter to create microscopic pores in cell membranes, providing also the basis for electroporation [31]. The latter treatment technology has important implications for cardiac patients and a series of recent studies have been devoted to its various aspects, including the observed effects of electroporation pulses delivered in close vicinity of the cardiac Sundeep Singh and Roderick Melnik pacemaker or its electrodes [32]. Moreover, recent advances in cardiac electrophysiology and related ablation procedures may lead to the development of new biomarkers for patients with heart disease [33].…”
Section: Ablation Modalities and Related Experimental Studiesmentioning
confidence: 99%